Effective generation of tumor-infiltrating lymphocyte products from metastatic non-small-cell lung cancer (NSCLC) lesions irrespective of location and previous treatments. (September 2022) - Castenmiller, S.M.; de Groot, R.; Guislain, A.; Monkhorst, K.; Hartemink, K.J.; Veenhof, A.A.F.A.; Smit, E.F.; Haanen, J.B.A.G.; Wolkers, M.C.
Abstract : Background: Non-small-cell lung cancer (NSCLC) is the leading cause of cancer-related mortality worldwide. Because current treatment regimens show limited success rates, alternative therapeutic approaches are needed. We recently showed that treatment-naïve, stage I/II primary NSCLC tumors contain a high percentage of tumor-reactive T cells, and that these tumor-reactive T cells can be effectively expanded and used for the generation of autologous tumor-infiltrating T cell (TIL) therapy. Whether these promising findings also hold true for metastatic lesions is unknown yet critical for translation into the clinic. Materials and methods: We studied the lymphocyte composition using flow cytometry from 27 metastatic NSCLC lesions obtained from different locations and from patients with different histories of treatment regimens. We determined the expansion capacity of TILs with the clinically approved protocol, and measured their capacity to produce the key pro-inflammatory cytokines interferon-γ, tumor necrosis factor and interleukin 2 and to express CD137 upon co-culture of expanded TILs with the autologous tumor digest. Results: The overall number and composition of lymphocyte infiltrates from the various metastatic lesions was by and large comparable to that of early-stage primary NSCLC tumors. We effectively expanded TILs from all metastatic NSCLC lesions to numbers that were compatible with TIL transfusion, irrespective of the location of the metastasis and of the previous treatment. Importantly, 16 of 21 (76%) tested TIL products displayed antitumoral activity, and several contained polyfunctional T cells. Conclusions: Metastatic NSCLC lesions constitute a viable source for the generation of tumor-reactive TIL products for therapeutic purposes irrespective of their location and the pre-treatment regimens. Highlights: T cells can be efficiently isolated and expanded from late-stage NSCLC lesions. TIL products from metastatic NSCLC lesions are polyfunctional. Metastatic location or pre-treatment regimen does not affect T cells. Adoptive TIL therapy is a therapeutic option for late-stage NSCLC patients.